2018
DOI: 10.1136/jech-2017-209948
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to traffic-related air pollution and acute bronchitis in children: season and age as modifiers

Abstract: A significant association of traffic-related air pollution and increased department visits for childhood AB was observed, notably in school-age children and during the cold season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 43 publications
4
27
0
1
Order By: Relevance
“…Previous literatures [18, 19] has suggested there were effect modifications for age, gender and season when investigating the effects of air pollution on hospital visits. Therefore, additional analyses were conducted to explore the potential modifications by age, gender and season subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…Previous literatures [18, 19] has suggested there were effect modifications for age, gender and season when investigating the effects of air pollution on hospital visits. Therefore, additional analyses were conducted to explore the potential modifications by age, gender and season subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we found that exposure to PM 2.5 and PM 10 had significantly instant effects on outpatient visits, and the effects lasted for 5–6 days and peaked at 3 days later. Previous studies have been found that PM had instant effect [25], lag effect [26, 27] or both effects [28] on outpatient visits for RDs. The difference of these conclusions might due to study population, sample size, or statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…In China, studies found a clear relation between air pollution and the increasing number of cases of respiratory diseases. Bai et al (2018) found a significant relationship between traffic-related air pollution and hospital visits for childhood Acute Bronchitis (AB), particularly in school-age children during cold seasons. It was found that an interquartile range increase in concentrations of NO 2 , PM 2.5 , and CO would significantly increase the daily hospital visits of childhood AB with 4-day cumulative effect (Bai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%